Neoadjuvant Chemoradiotherapy and Liver Transplantation for Unresectable Hilar Cholangiocarcinoma: The Irish Experience of the Mayo Protocol. Issue 10 (October 2020) - Zaborowski, Alexandra; Heneghan, Helen M.; Fiore, Barbara; Stafford, Anthony; Gallagher, Tom; Geoghegan, Justin; Maguire, Donal; Hoti, Emir
Abstract : Background: Pioneered by the Mayo Clinic, multimodal therapy with neoadjuvant chemoradiotherapy and orthotopic liver transplant has emerged as a promising option for unresectable hilar cholangiocarcinoma (hCCA). This study reports the experience of the Irish National Liver Transplant Programme with the Mayo Protocol. Methods: All patients diagnosed with unresectable hCCA between 2004 and 2016, who were eligible for the treatment protocol, were prospectively studied. Results: Thirty-seven patients commenced chemoradiotherapy. Of those, 11 were excluded due to disease progression and 26 proceeded to liver transplantation. There were 24 males, the median age was 49, and 88% had underlying primary sclerosing cholangitis. R0 and pathologic complete response rates were 96% and 62%, respectively. Overall median survival was 53 months and 1-, 3-, and 5-year survival was 81%, 69%, and 55%, respectively. The median survival of patients achieving a pathologic complete response was 83.8 months compared with 20.9 months in the group with residual disease ( P = 0.036). Six patients (23%) developed disease recurrence. Among the patients who developed metastatic disease during neoadjuvant treatment, median survival was 10.5 months compared with 53 months in patients who proceeded to transplant ( P < 0.001). Conclusions: Neoadjuvant chemoradiotherapy followed by liver transplantation substantially increases the survival of patients with unresectable hCCA. Achieving a pathologic complete response confers a significant survival benefit.